Addressing high frequency effects in VLSI interconnects with full wave model and CFH - Achar, Ramachandra; Nakhla, Michel S.; Zhang, Q. J. (Proceedings of the 1995 IEEE/ACM international conference on Computer-aided design, 1995)
In order to accurately characterize dispersive system of VLSI interconnects at higher frequencies, full wave analysis which takes into account all possible field components and satisfies all boundary conditions is required. However, conventional circuit simulation of interconnects with full wave models is extremely CPU expensive. This paper presents a new method to extend the moment matching technique, complex frequency hopping, to the case of interconnects modeled with full wave analysis. Formulation of circuit equations is modified to incorporate interconnect stencil from full wave analysis. A new algorithm for the moment generation for interconnect networks with full wave models has been developed. Full wave analysis has been carried out with the efficient 'spectral domain approach'. Results have shown that the proposed method is accurate while it yields a speed up of one to three orders of magnitude over conventional simulation techniques. Subject Terms: circuit analysis computing; VLSI; integrated circuit interconnections; circuit CAD; high-frequency effects; VLSI interconnects; high frequency effects; full wave model; CFH; spectral domain approach; dispersive system; full wave analysis; boundary conditions; moment matching technique; complex frequency hopping